Dietetyka w De re coquinaria - Kokoszko, Maciej; Rzeźnicka, Zofia (Przegląd Nauk Historycznych, 2011)
The article tries to demonstrate connections of De re coquinaria with the results of the ancient and Byzantine research into dietetics. First, the authors present an overview of the established doctrines on the role of food in preserving human health. They resort to the Hippocratic and Galenic teachings, as well as exemplifying the presence of the dietetic knowledge in the literature of Antiquity and Byzantium (first and foremost in Deipnosophists by Atenaeus of Naucrats, De observatione ciborum by Anthimus and in Geoponica). Subsequently, they analyze select fragments from De coquinaria (i.e. the recipes for sauces [oxyporum, oxygarum digesti bile, oenogarum], flavoured salts, sales conditi, spiced wine, conditum paradoxum, honey wine, conditum melizomum viatorum, Roman absinth, absintium Romanum, rose wine, rosatum, vegetable purée, pulmentarium, the soups called tisana vel sucus and tisana barrica, and finally the commentary on nettles), and show their analogies to the doctrines present in medical writings (mostly to those by Galen, Orybasius and Aetius of Amida).